2013
DOI: 10.1039/c2nj40877e
|View full text |Cite
|
Sign up to set email alerts
|

Non-symmetric substituted ureas locked in an (E,Z) conformation: an unusual anion binding via supramolecular assembly

Abstract: The chemical composition of the essential oil of the Sardinian dwarf curry plant [Helichrysum italicum G. Don ssp. microphyllum (Willd) Nym] was studied. Genetic analysis suggested the presence of two chemotypes; morphological and chemical differences confirmed the presence of two chemotypes (A and B). The maximum yields were 0.18 and 0.04% (v/w) for flowering tops and stems, respectively. The concentrations of nerol and its esters (acetate and propionate), limonene, and linalool reach their highest values dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Initially we considered a syn / anti conformational changes in the thiourea group, 57,58 however a review of the literature reveals that similar anomalies have been reported with dihydrogenphosphate, and not just with thioureas and urea based systems. 25,30,59,60 It appears that the binding of a second H 2 PO 4 − strengthens the interaction with the first unit, and that acetate can show similar behaviour in certain instances.…”
Section: Discussionmentioning
confidence: 99%
“…Initially we considered a syn / anti conformational changes in the thiourea group, 57,58 however a review of the literature reveals that similar anomalies have been reported with dihydrogenphosphate, and not just with thioureas and urea based systems. 25,30,59,60 It appears that the binding of a second H 2 PO 4 − strengthens the interaction with the first unit, and that acetate can show similar behaviour in certain instances.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structures with Z′ > 1 are quite common; among others, Anderson et al 12 point out that, although many factors may contribute to the crystallization of molecule with Z′ > 1, there is no general rule to explain this phenomenon. In this case, the absence of any specific intramolecular interaction in the [Zn(MeImSH) 2 I 2 ] complex, which generally might favour some specific conformations, 13 could determine a certain degree of conformational flexibility in solution. Desiraju 14 defined a crystal with Z′ > 1 as a "kinetic form which has been trapped before the molecules have adjusted themselves in their final orientations".…”
Section: Packing Analysismentioning
confidence: 99%
“…FT-Infrared spectra of powdered samples were measured using a Thermo-Nicolet 5700 spectrometer from 4000-400 cm −1 in the form of pressed KBr pellets. 13 C NMR spectra were recorded using a Varian 400 MHz spectrometer, chemical shifts are reported in ppm (δ) downfield from TMS using the same solvent as the internal reference; 13 C NMR MAS spectra were calibrated such that the observed up field peak in the spectrum of adamantane is set to δ = 31.47. All of the low resolution mass spectra were recorded by electrospray ionisation using a Fisons VG platform instrument or a Waters ZMD quadrupole mass spectrometer in HPLC grade acetonitrile.…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…Thus this simple model may be a structure of choice [ 32 ] to study the interactions of amides with acids and carboxylates taking into account the substituent effect. The carboxylates were used in several studies as anions that probe the non-covalent interactions [ 19 , 33 , 34 ]. The regular substituent-dependent changes in properties of carboxylic acids and thus benzoates are commonly known.…”
Section: Introductionmentioning
confidence: 99%
“…The acidity and thus donation ability of the hydrogen bond donor (OH) in -COOH moiety in acids may be a good test for description of interaction preferences driven by the character of the substituent. On the other hand the basicity and thus the ability of being an acceptor for hydrogen bonds as in phenolates [ 35 38 ] of carboxylates [ 19 , 33 , 34 ] may be used in a similar way. In 4-substituted benzoates, however, both oxygen atoms are equal in the light of hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%